2020
DOI: 10.3389/fnhum.2020.00322
|View full text |Cite
|
Sign up to set email alerts
|

Economical Assessment of Working Memory and Response Inhibition in ADHD Using a Combined n-back/Nogo Paradigm: An ERP Study

Abstract: The development of cognitive interventions in attention-deficit/hyperactivity disorder (ADHD) often requires the assessment of multiple cognitive functions. However, experimental settings consisting of various tasks are particularly strenuous for patients and can thus result in poor data quality. For the economical assessment of working memory and response inhibition, this study aims to validate a combined n-back/nogo paradigm by comparing it to single task versions and to demonstrate its applicability for ADH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…While the N-Back Task method, used by [7] [15] and [16] in their research works, focuses on the development of individual exercises to reinforce memory and concentration that involve repetitive activities to measure their performance. Such is the case of Breitling [16], which used the method to validate its efficiency with two groups of children with ADHD. Authors concluded that the N-Back Task serves to measure the memory level of a person as well as improve its performance.…”
Section: Methods For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…While the N-Back Task method, used by [7] [15] and [16] in their research works, focuses on the development of individual exercises to reinforce memory and concentration that involve repetitive activities to measure their performance. Such is the case of Breitling [16], which used the method to validate its efficiency with two groups of children with ADHD. Authors concluded that the N-Back Task serves to measure the memory level of a person as well as improve its performance.…”
Section: Methods For Learningmentioning
confidence: 99%
“…From the literature, 90% of the articles had in common the use of gamification in developing their research to improve children's memory. Among these, we can highlight the N-Back Task, which measures and reinforces children's visual motor memory, concentration, and intelligence [16]. However, compared with the TCT method, the N-Back Task focuses on just one kind of game, while the TCT allows a wider variety of games to be used depending on the cognitive area they want to improve or reinforce.…”
Section: About the Methodologymentioning
confidence: 99%
“…The performance related to visual working memory was calculated as the percentage of correct hits (hits on target-falsely reported nontarget), with larger values indicating better performance. The performance related to auditory working memory was inversely proportional to the NoGo commission error rate (100%-NoGo stimulus false alarm rate), with larger values indicating better performance [ 54 ]. Finally, the size of an effect (SE), r pb 2 = t 2 /( t 2 + df ) was used to test the effects of audiovisual interactions on working memory.…”
Section: Methodsmentioning
confidence: 99%
“…According to this study, ADHD patients reported lower n-back and nogo P3 amplitudes, increased omission mistakes, and reaction times. Memory tasks and response control impairments in ADHD patients can be assessed using the n-back/nogo task [47].…”
Section: Electroencephalographic and Topographical Distribution Of Th...mentioning
confidence: 99%